2019
DOI: 10.3390/agronomy9090521
|View full text |Cite
|
Sign up to set email alerts
|

Regulated Deficit Irrigation as a Water-Saving Strategy for Onion Cultivation in Mediterranean Conditions

Abstract: Field experiments were performed for two growing seasons in Spain under Mediterranean conditions to evaluate the response of onion growth, plant water status, bulb yield, irrigation water use efficiency (IWUE), and gross revenue to regulated deficit irrigation strategies (RDI). Seven irrigation treatments were utilized, including the application of 100% irrigation water requirements (IWR) during the entire growing season and the application of 75% or 50% of the IWR during one of the following growth stages: th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 51 publications
4
8
0
Order By: Relevance
“…In the Mediterranean region, water resources are scarce, which calls for the need to reassess current water use practices. The increasing population growth leads to an increase in the demand for food, which increases the irrigated area, which has increased eight-fold over the past century [ 3 , 4 , 5 ]. These restrictions and risks to food security will be massive, particularly with the expected climate change, causing increased competition for water resources between different sectors [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the Mediterranean region, water resources are scarce, which calls for the need to reassess current water use practices. The increasing population growth leads to an increase in the demand for food, which increases the irrigated area, which has increased eight-fold over the past century [ 3 , 4 , 5 ]. These restrictions and risks to food security will be massive, particularly with the expected climate change, causing increased competition for water resources between different sectors [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to an estimation, 40% of agricultural production and yield is based on irrigation. However, the growing population is one of the causes to increase in food consumption, which expands the irrigated area by eight times in the past 100 years and ultimately leads to drought conditions [4,5]. These prevailing circumstances will increase the water scarcity and food security risk that badly affect the world economy on a larger scale.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, multiple regression analysis was used to analyze environmental factors and their impact on crop yields. Sixth, Abdelkhalik and colleagues [7] conducted field experiments on two farming stages in Spain to evaluate how effective controlled deficit different irrigation water facilities are for onion growth and total yields. They found that deficit irrigation strategies have reduced marketable yields.…”
Section: Related Workmentioning
confidence: 99%